The fall and rebound of average establishment size in West Germany - Tim Kovalenko; Timo Sauerbier; Benedikt Schröpf (Deutsche Bundesbank, 2024)
In West Germany, the average size of establishments declined during the 1990s and started to increase again in the late 2000s, while the employer size wage premium followed the opposite trajectory. In this paper, we show that these two developments are interrelated. More precisely, our results suggest that variations in the employer size wage premiums induced establishments to vary their employment level, consistent with monopsony power on the labor market. Moreover, our regional analyses show that average establishment size correlates positively with GDP per capita. We rationalize these findings with a heterogeneous firms model with monopsonistic competition in the labor market, stemming from the household's love-of-variety preferences for employers. Both empirics and theory reveal that higher size wage premiums decrease average establishment size by downsizing incumbent establishments and triggering the entry of small establishments, thus also negatively affecting aggregate productivity.
Keywords: E24; J31; J42; L25; 330; Establishment Size; Size Wage Premium; Productivity; Labor MarketPower; Germany